2021
DOI: 10.1007/s10856-020-06474-7
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiomyocyte-derived exosomes induce cardiac gene expressions in mesenchymal stromal cells within 3D hyaluronic acid hydrogels and in dose-dependent manner

Abstract: Accomplishing a reliable lineage-specific differentiation of stem cells is vital in tissue engineering applications, however, this need remained unmet. Extracellular nanovesicles (particularly exosomes) have previously been shown to have this potential owing to their rich biochemical content including proteins, nucleic acids and metabolites. In this work, the potential of human cardiomyocytes-derived exosomes to induce in vitro cardiac gene expressions in human mesenchymal stem cells (hMSCs) was evaluated. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In addition, HA is widely present in connective tissues, and studies have indicated that HA hydrogels can provide sites for cell proliferation and differentiation; therefore, HA is widely used in tissue repair and reconstruction applications [ 84 , 85 ]. Burak Derkus [ 86 ] used HA hydrogels loaded with human cardiomyocyte-derived EVs and finds that they can induce the expression of heart-related genes in MSC.…”
Section: Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HA is widely present in connective tissues, and studies have indicated that HA hydrogels can provide sites for cell proliferation and differentiation; therefore, HA is widely used in tissue repair and reconstruction applications [ 84 , 85 ]. Burak Derkus [ 86 ] used HA hydrogels loaded with human cardiomyocyte-derived EVs and finds that they can induce the expression of heart-related genes in MSC.…”
Section: Hydrogelsmentioning
confidence: 99%
“… [ 97 ] HA-tyramine (HA-Tyr) human cardiomyocyte 50 ​nm 5 days 3% HA-Tyr: retained almost half of EVs in the first 2 days, while the cumulative release was found until nearly 5 days. [ 86 ] Self-assembling peptides (SAPs) BMSC 120.1 ​± ​55.4 ​nm 168 ​h The release rate of EVs was dose-dependently accelerated in the presence of MMP2 compared to the blank group. [ 23 ] Atom transfer radical polymerization (ATRP) nonactivated macrophages J774A.1 30–150 ​nm up to one month The monomer-to-crosslinker ratio (molar ratio) and the crosslinking density of the polymer networks both affect the release of EVs.…”
Section: Underlying Mechanisms Affecting the Loading And Release Of Evsmentioning
confidence: 99%
“…Exosomes were isolated from polarized (M1, M2, PdNPsinduced) and non-polarized macrophages (M0), using a previously described protocol, which has been successfully applied in various studies. [29][30][31] Initially, serum-free conditioned media (CM) were collected from different macrophage groups: (i) unpolarized (M0), (ii) M1 induced by LPS (200 ng ml −1 ) and IFN-γ (20 ng ml −1 ), (iii) M2 induced by IL-10 (20 ng ml −1 ), and (iv) M1-like induced by PdNPs (50 μg ml −1 ). The CM was then subjected to a series of centrifugation steps at 300g (5 min), 3000g (15 min), and 10 000g (15 min) at 4 °C.…”
Section: Exosome Isolation and Characterizationmentioning
confidence: 99%
“…Copyright 2019 Royal Society of Chemistry. Adapted with permission under a creative commons CC-BY license 4.0 from ref . Published 2021 by Springer Nature.…”
Section: Exosomes For Cvd Prevention and Treatmentmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) exosomes are paracrine factors in stem cells for cardiac regeneration . Human umbilical MSC exosomes were encapsulated in a functional peptide hydrogel for cardiac repair, and a three-dimensional hyaluronic acid hydrogel was used for loading of human cardiomyocyte-derived exosomes . There is also an injectable hydrogel to repair the injured heart …”
Section: Exosomes For Cvd Prevention and Treatmentmentioning
confidence: 99%